Hard Work and Responsibility in 2 Thessalonians 3:10 - Cosmas Janson Galaliza (Uganda Christian University, 2025)
This study investigates the themes of hard work and personal responsibility as expressed in 2 Thessalonians 3:10, with particular attention to the apostolic instruction: “If anyone is not willing to work, let him not eat.”(ESV). Employing a library-based methodology, the research engages in exegetical analysis of the passage within its historical and literary context, supported by a survey of biblical commentaries, theological literature, and socio-historical studies. The paper explores how Paul addresses issues of idleness and disorderly conduct in the Thessalonian community, situating the instruction within the broader framework of Pauline ethics and eschatological expectation. The findings suggest that the apostle’s exhortation was not merely a response to economic laziness, but a pastoral correction aimed at restoring communal order and theological integrity. This study further considers the relevance of Paul’s teaching for contemporary Christian understandings of work ethics, social responsibility, and the dignity of labor.
Undergraduate